(untitled) (Dhaka University Journal of Science, 2012)
The photodegradation of orange green (OG) by excitation of Fe (III)-aqua complexes has been investigated under UV and solar light illumination. The rate of degradation has been found to be strongly influenced by the pH of the solution, initial concentration of Fe(III) and the nature of the light sources. The progress of removal of OG from solution has been monitored by recording the change of absorbance at ?max = 480 nm, (? = 1.27 × 104 L mol-1cm-1 at 30°C), with time. The pH has been varied from 1.2 to 3.5. The initial concentration of Fe (III) was between 9.0 × 10-4 mol L-1 and 2.4 × 10-3 mol L-1. The intensity of the UV artificial source was 14 Wm-2, whereas the average intensity of the solar light during the experiments was about 700 Wm-2. An optimistic result was obtained, when OG was irradiated by solar light. About 92% degradation of 1.5 × 104 mol L-1 OG solution has been done within 70 minutes by photodegradation using Fe(III)-aqua complex at pH 2.5 by UV light whereas about 86% degradation has been recorded by the solar light under the same conditions. DOI: http://dx.doi.org/10.3329/dujs.v60i1.10334 Dhaka Univ. J. Sci. 60(1): 43-46 2012 (January)